2013
DOI: 10.1093/jjco/hyt096
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Metastatic Urothelial Carcinoma Undergoing Cisplatin-based Salvage Chemotherapy

Abstract: Objective: To assess the clinicopathologic factors influencing survival in patients with metastatic urothelial carcinoma undergoing salvage chemotherapy. Methods: A retrospective review was conducted on cases of metastatic urothelial carcinoma who underwent cisplatin-based salvage chemotherapy at our institution between April 2003 and July 2011. The association of various clinicopathologic factors with survival was assessed. Survival curves were constructed by the Kaplan -Meier method. A log-rank test for univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Previous literatures have shown the survival prediction for metastatic UC after chemotherapy, mainly focusing on UCB [18][19][20][21][22][23][24][25][26]. There were limited studies to separately investigate or compare the prognostic factors between metastatic UTUC and UCB after cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures have shown the survival prediction for metastatic UC after chemotherapy, mainly focusing on UCB [18][19][20][21][22][23][24][25][26]. There were limited studies to separately investigate or compare the prognostic factors between metastatic UTUC and UCB after cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that higher leukocyte counts, poor performance status and liver metastasis were independent poor prognostic factors for metastatic UC in a Japanese, retrospective, single-institutional study. 3 NLR has recently been shown to be a prognostic factor in many malignancies. 4 Regarding UC, there are several reports of patients with upper urinary tract UC [5][6][7][8][9] and a few in patients with bladder cancer undergoing radical cystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, von der Maase et al (4) showed that KPS < 80%, the presence of visceral metastasis, elevated alkaline phosphatase and the number of disease sites (>3) were significant prognostic parameters in patients with locally advanced or metastatic UC treated with GC or MVAC. Furthermore, we have recently reported that liver metastasis, poor performance status and higher leukocyte counts were independent poor prognostic factors for metastatic UC (25). On the other hand, studies concerning prognostic factors after failure of first-line salvage treatment are lacking.…”
Section: Discussionmentioning
confidence: 98%